RNA-seq analysis reveals key genes associated with downregulation of APE1 in esophageal squamous cell carcinoma - Chu, Alan; Liu, Xiao; Liu, Shijia; Li, Mengxi; Song, Rui; Gan, Lanlan; Wang, Yongtai; Liu, Zongwen; Sun, Chen (Frontiers in Genetics, 2025)
ObjectiveThis study aims to explore the impact of APE1 gene knockout on the transcriptome of esophageal cancer cells and conduct a preliminary screening of APE1-regulated target genes to provide a basis for understanding APE1 target genes and finding new anti-esophageal cancer therapeutic targets.MethodsWe collected 100 patients with esophageal squamous cell carcinoma (ESCC), analyzed the expression of APE1 in ESCC by immunohistochemical, and analyzed the overall survival. TE-1 cells with APE1 knockout were used for transcriptome sequencing (RNA sequencing, RNA-Seq) detection, and GO and KEGG enrichment analysis of differentially expressed genes was conducted. Protein-protein interaction (PPI) network analysis was performed on the genes in the intersection of differential genes between the two sequencing datasets. The qRT-PCR and Western blotting experiments were employed to confirm the effect of APE1 knockdown on the expression levels of FN1, TNF, and IL-6 in esophageal cancer cells.ResultsAPE1 highly expressed in ESCC tissue, and its high expression leads the worse OS. The stable transfected TE-1 cell line with knockdown of the APE1 gene was successfully constructed, with a knockdown efficiency of 100%. RNA-seq analysis revealed that 2,060 differential genes were detected between APE1-KO stably transfected cells and their corresponding APE1-YD cells, with 1,063 upregulated genes and 997 downregulated genes. RNA-seq analysis found that differentially expressed genes after APE1 knockout in TE-1 cells were primarily enriched in pathways related to metabolism, extracellular matrix, inflammatory response, and angiogenesis. PPI network analysis demonstrated that FN1, TNF, and IL-6 may be essential target genes of APE1. The three core genes of FN1, TNF, and IL-6 were confirmed using qRT-PCR and Western blotting, and the results were consistent with the transcriptome sequencing results.ConclusionKnocking out APE1 can affect the function, related pathways, and downstream target gene expression of ESCC cells. APE1 can promote the transcriptional expressions of FN1 and IL6 genes while inhibiting the TNF gene. FN1, TNF, and IL-6 may be potential target genes regulated by APE1 in esophageal cancer.